Decisions, games, and markets - Battigalli, Pierpaolo; Montesano, Aldo.; Panunzi, Fausto (Boston : Kluwer Academic, 1997)
Decisions, Games and Markets is designed to stimulate new developments in decision theory, game theory and general equilibrium theory, as well as their applications to economics. The book is divided into three parts - Decision Theory, Game Theory, and the Theory of Markets. Though its orientation is primarily methodological, some articles are more applied. The consistent use of formal analysis and methodological individualism constitute the unifying theme of the book.
Decisions, Games and Markets will be of considerable interest to both students and teachers of microeconomics and game and decision theory.
11. Economic Models of Social Learning / Giuseppe Moscarini and Marco Ottaviani -- 12. Market Size, the Informational Content of Stock Prices and Risk: A Multiasset Model and Some Evidence / Marco Pagano -- 13. Adoption of Flexible Technologies in an Evolutionary Environment / Pier Luigi Sacco and Carlo Scarpa.
Includes bibliographical references and index.
Keywords: Decision making; Game theory; Markets; Equilibrium (Economics)